Seroprotein Patterns in the Bufo marinus Complex - Bertini, F. (1962)
The systematic relationships of the large species of neotropical toads of the Bufo marinus complex have not been defined since the studies of Lutz (1925). On the basis of recent contributions (Lutz and Kloss, 1952; Cochran, 1955; and Vellard, 1959) the following fundamental taxonomic units can be recognized: 1) an Amazonian population extending north to Mexico, corresponding to Bufo m. marinus (Linnaeus) with some subspecies bordering its range, as B. marinus poeppigii (Tschudi); 2) a well-defined eastern form, Bufo ictericus Spix, from the humid coastal Brasilian realm; 3) a central, latitudinally widespread giant form, Bufo paracnemis Lutz, adapted to the dry and open uplands or catingas; 4) two closely related southern and southeastern forms, Bufo arenarum Hensel extending from Matto Grosso and Rio Grande do Sul to the paragonian meseta of Rio Negro, and Bufo ruf us Garman in the Brasilian states of Matto Grosso and Minas Gerais (see Fig. 1). The specific interrelation of B. arenarum and B. rufus have not been studied. Bufo ictericus and B. paracnemis were formerly described as geographical forms of B. marinus (Müller, 1927; Mertens, 1930; Müller and Hellmich, 1936; Lutz and Kloss, 1952) but their specific status was recently re-evaluated (Cochran, 1955). Bufo paracnemis appears to be sympatric with B. arenarum, B. rufus and B. ictericus. B. ictericus is probably sympatric with B. arenarum and B. rufus. Recent studies (Buzzati-Traverso and Rechnitzer, 1953; Lanza and Antonini, 1955; Dessauer and Fox, 1956; Boyden and Paulsen, 1957; Zweig and Crenshaw, 1957; Van Sande and Kar- cher, 1960), indicate the value of biophysical tests in elucidating the relationship of closely related species. The studies here reported are an attempt to check independently the status of the species of the Bufo marinus complex by an electrophoretic analysis of the seroproteins.